Two-dimensional flow properties of micronozzle under varied isothermal wall conditions - Hameed, Amar Hasan; Kafafy, Raed; Asrar, Waqar; Idres, Moumen (2011)
A new technology which uses thermoelectric elements for the walls of microthrusters is emerging. The solid state walls act as either flow heater or cooler based on the local flow Mach number to achieve maximum acceleration of the flow throughout the micronozzle. This technique can improve the performance of low-Reynolds-number microthrusters which typically suffer from high viscous losses and low thrust efficiency. Extensive analytical and experimental investigation is still required to assess the potential of the new technology. In the present paper, we focus on the direct effect of using thermoelements to control the temperature of the walls of a micronozzle. Continuum flow is assumed where Knudsen number is sufficiently large due to the selected range of flow properties and micronozzle size. Viscous compressible laminar flow is solved in the micronozzle with selected wall temperature profiles. The temperature difference between the wall and the gas effects the static temperature and static pressure profile, Mach number is increased, density near the wall is increased due to cooling. Alleviation of viscous losses by cooling the supersonic flow in the expander has been clearly demonstrated. Overall performance parameters of the thermoelectrically controlled microthruster has been evaluated and compared against the performance of conventional micro cold gas thrusters and micro-resistojets for several propellants.